2021
DOI: 10.3390/vaccines9101125
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Persistence 6 Months Post-Vaccination with BNT162b2 among Health Care Workers

Abstract: Background: We present immunogenicity data 6 months after the first dose of BNT162b2 in correlation with age, gender, BMI, comorbidities and previous SARS-CoV-2 infection. Methods: An immunogenicity evaluation was carried out among health care workers (HCW) vaccinated at the Istituti Fisioterapici Ospitalieri (IFO). All HCW were asked to be vaccine by the national vaccine campaign at the beginning of 2021. Serum samples were collected on day 1 just prior to the first dose of the vaccine and on day 21 just prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 24 publications
12
31
1
Order By: Relevance
“…The most interesting point of this study refers to the kinetics of the antibody titers. In previous reports in healthy participants, antibody titers stayed relatively stable in the first months after vaccination, although a certain decay was observed [ 26 , 27 , 28 , 29 , 30 , 31 ]. In our cohort, the dynamics of antibody titers also showed relative stability in the group of HCW.…”
Section: Discussionmentioning
confidence: 89%
“…The most interesting point of this study refers to the kinetics of the antibody titers. In previous reports in healthy participants, antibody titers stayed relatively stable in the first months after vaccination, although a certain decay was observed [ 26 , 27 , 28 , 29 , 30 , 31 ]. In our cohort, the dynamics of antibody titers also showed relative stability in the group of HCW.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, multiple studies have shown waning immunity acquired after vaccination, especially in immunocompromised patients, for example those undergoing hemodialysis or cytotoxic cancer drug treatment. This contributes to an increasing number of breakthrough infections ( Shroff et al, 2021 ; Juno and Wheatley, 2021 ; Goldberg et al, 2021 ; Fowlkes et al, 2021 ; Davidovic et al, 2021 ; Campo et al, 2021 ). Currently, several countries have developed various strategies to tackle this problem, among which, additional doses of COVID-19 vaccines have shown to be safe and efficient in boosting immune response ( Yue et al, 2021 ; Falsey et al, 2021 ; Dekervel et al, 2021 ; Choi et al, 2021 ; Barros-Martins et al, 2021 ).…”
Section: Vaccinesmentioning
confidence: 99%
“…Among the four journal articles included in this study, two reported that seropositive groups had a larger percent decline in Ab titers from peak compared with seronegative groups. 10,12 This is possibly due to higher peak values making Ab catabolism more pronounced in seropositive groups. 12 Another possible explanation is due to timing, as seropositive groups reach peak Ab titers right after the first dose.…”
Section: Serostatusmentioning
confidence: 99%
“…9 Such vulnerability is correlated to the significant decline in anti-SARS-CoV-2 antibodies (Abs) over time. [10][11][12] This waning humoral response could lead to breakthrough infections, thus highlighting the potential role of serologic testing to assess vaccine immunogenicity and protection efficacy. While the role of T cells and B memory cells from vaccine-induced immunity has yet to be fully elucidated, multiple studies showed that Ab levels directly correlate with risk of vaccine reinfection and breakthrough, with low levels of anti-SARS-CoV-2 IgG in patients with infections correlating with high viral load and duration of viral shedding.…”
Section: Introductionmentioning
confidence: 99%